Challenges Smart Grid in Blockchain Applications - Immaniar, Dewi; Aryani, Anna Ayu; Ula, Shinta Zahrotul; Firmansyah, Muhamad Rizky; Rahman, Yudi (IAIC Bangun Bangsa, 2023)
Globally, interest in renewable energy has grown recently. The microgrid integrates traditional dispersed energy resources utilizing technological tools and information technology, making it more effective and flexible to enhance the economic and environmental situations (IT). One of these technologies that has drawn interest in microgrid applications to create a sustainable society is blockchain. The blockchain idea can offer immutability for microgrid transactions such as recording power generation levels and confirming transactions between generators and end consumers. By eliminating the need to connect with third parties, blockchain-based smart contracts can be utilized for auditing or resolving a transaction dispute between the producers and the users. In this paper, we highlight many recent research projects on blockchain applications in microgrids and the use of smart contracts to enhance the transactive resilience in microgrids.